Os serviços de atenção (na rua) à população em situação de rua em Vitória : uma história contada em três tempos - Marins, Lívia Ferreira Cardoso (2013)
This research sought to understand how historically was constituted in Vitória-ES the need of municipal government set up a network of services to the attention of the adult population in the streets. Therefore, we used oral history interviews in which subjects addressed by nine workers who organized later in Victoria as a Service Specializing in Social Approach. Analyzes the history that will constitute this service through the concept of Social Enclave (Caldeira, 2011) and the notion Foucaultian (2008) regarding the security mechanisms in the management of cities.